TECHNOLOGY OF AN ENVIRONMENTALLY SAFE GAS CHEMICAL COMPLEX FOR UTILIZATION OF SULFUR-CONTAINING AND FLARE GASES DISCHARGED FROM TECHNOLOGICAL INSTALLATIONS (American Journal of Pedagogical and Educational Research, 2023)
A schematic diagram of an environmentally safe HCG is presented, which provides practically waste-free processing of sulfur-containing natural gas.